A polynomial representation of 6.3 μm water vapor and 4.3 μm CO2 atmospheric transmissivities - Minnis, Patrick, author; Cox, Stephen K., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1976)
The research reported in this paper describes a polynomial model formulated for the depiction of 6.3 μm H2O and 4.3 μm CO2 transmissivities in the atmosphere. A six degree function utilizing a corrected optical path is found sufficient for expressing convolved tabulated transmittance data of 10 cm-1 resolution, with an RMS error of about one percent transmission. With this model transmissivities may be calculated for many spectral intervals in a relatively small amount of time with the precision required for most atmospheric problems.
Polynomial representation of 6.3 mu m water vapor and 4.3 mu m CO2 atmospheric transmissivities
December 1976.
Keywords: Radiation transfer -- Mathematical models; Water vapor, Atmospheric; Atmospheric radiation -- Mathematical models; Atmospheric carbon dioxide